Pure-Tone Hearing Thresholds and Brainstem Auditory Evoked Potentials in Sporadic Ataxia - Zeigelboim,Bianca Simone (2020)
Abstract Introduction Spinocerebellar ataxia (SCA) is part of a genetic and clinical heteroge- neous group of neurodegenerative diseases characterized by progressive cerebellar ataxia. Objective To describe the results of audiological and electrophysiological hearing evaluations in patients with sporadic ataxia (SA). Methods A retrospective cross-sectional study was carried out with 11 patients submitted to the following procedures: anamnesis, otorhinolaryngological evaluation, tonal and vocal audiometry, acoustic immittance and brainstem auditory evoked potential (BAEP) tests. Results The patients presented with a prevalence of gait imbalance, of dysarthria, and of dysphagia; in the audiometric and BAEPs, four patients presented with alterations; in the acoustic immittance test, ﬁve patients presented with alterations, predominantly bilateral. Conclusion The most evident alterations in the audiological evaluation were the prevalence of the descending audiometric conﬁguration between the frequencies of 2 and 4 kHz and the absence of the acoustic reﬂex between the frequencies of 3 and 4 kHz bilaterally. In the electrophysiological evaluation, the patients presented changes with a prevalence of increased I, III and V wave latencies and the interval in the interpeak I-III, I-V and III-V. In the present study, it was observed that auditory complaints did not have a signiﬁcant prevalence in this type of ataxia, which does not occur in some types of autosomal recessive and dominant ataxia.